Reducing Postoperative Pain from Tonsillectomy Using Monopolar Electrocautery by Cooling the Oropharynx - Vieira,Lucas (2014)
Objective Evaluate intraoperative cooling of the oropharynx to reduce postoperative pain in tonsillectomy using monopolar electrocautery. Methods Sixty-six patients, age 1 to 12 years, were selected for the study, 33 in the control group and 33 in the experimental group. After randomization, patients underwent subcapsular dissection and hemostasis with monopolar electrocautery. Patients in the experimental group had the oropharynx cooled after tonsil dissection and hemostasis for 10 minutes. The procedure was done through the oral cavity by irrigation with 500 mL of 0.9% saline, in temperatures between 5°C and 10°C, for 5 minutes. The evaluation of postoperative pain was made with the pain visual analog scale (VAS) for 10 days. As complementary data on the evaluation of pain, we recorded daily use of ketoprofen for pain relief. Results Pain after tonsillectomy assessed by VAS was significantly lower in the experimental group at days 0, 5, and 6 (p < 0.05). There were no differences in the use of ketoprofen between the groups. Conclusion Cooling of the oropharynx after tonsillectomy promotes clinically significant reduction in postoperative pain, without additional complications.